Peningkatan Pemahaman Konsep Geometri melalui Tahapan Berpikir Van Hiele di SMP Negeri 8 Langsa - Putri Novita Sari; Sri Muliati (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
Understanding the concept is a benchmark students can proceed to the next stage in the learning process. Van Hiele's thinking stage is a solution to direct students to the actual concept of geometry. The purpose of this study was to determine whether there was an increase in understanding of the geometrical concepts of eighth grade students of SMPN 8 Langsa through Van Hiele thinking stages. This study used a One Group Pretest-Posttest Desaign research design. With a population of all eighth grade students of SMPN 8 Langsa, the sample was selected using a simple random sampling technique, namely grade VIII1 students. The instrument uses the ability to understand the ability of geometric concepts in the form of a description consisting of 6 questions. From the results of the calculation of the percentage of students understanding the concept of geometry shows an increase of 48%. The results of data analysis obtained that count> ttable is 12.59> 2.08, this means that Ho is rejected and Ha is accepted, so the conclusion obtained is that there is an increase in understanding of students' geometry concepts through the stages of van hiele thinking at SMPN 8 Langsa.